Strengthening regulation for medical products in Tanzania: An assessment of regulatory capacity development, 1978-2020. - Adam M Fimbo; Hiiti B Sillo; Alex Nkayamba; Sunday Kisoma; Yonah Hebron Mwalwisi; Rafiu Idris; Sarah Asiimwe; Patrick Githendu; Osondu Ogbuoji; Linden Morrison; Jesse B Bump; Eliangiringa Kaale (PLOS Global Public Health)
Improving medicines regulation can lead to better population health, but how this process works in low- and middle-income countries remains underexplored. Tanzania's pharmaceutical sector is often cited as a successful example of a well-functioning regulatory system in a developing country, attributed to the work of the Tanzania Food and Drugs Authority (TFDA), now the Tanzania Medicines and Medical Devices Authority (TMDA). This raises the question: how was this regulatory capacity developed, and what lessons can other countries learn from Tanzania's experience? This paper analyzes changes in Tanzania's pharmaceutical regulation over three periods of significant sectoral reform. A desk review was conducted of Tanzania's policies, laws, regulations, guidelines, procedures, and institutional reports. The study reveals that Tanzania's regulatory capacity improved significantly through targeted reforms that addressed challenges in key regulatory areas. The three key periods examined are: 1) The separation of medicines regulation from food safety (1978-2003), 2) The expansion of regulatory domains and the establishment of a semi-autonomous regulatory agency (2003-2011), and 3) The expanded role of the Pharmacy Council to include premises regulation (2011-2020). The development of a well-functioning regulatory system in Tanzania resulted from advancements in four key areas: 1) The evolution of a legal regulatory framework, 2) Strong stakeholder engagement, 3) Continuous capacity building, and 4) Effective organizational leadership. Tanzania's regulatory system has evolved from being relatively ineffective to leading regional harmonization efforts in East Africa. This progress was not linear, requiring sustained effort, collaboration, and support from key development partners such as the Global Fund, WHO, and UNDP. Future efforts to enhance regulatory effectiveness should focus on creating adaptive systems that respond to changing needs, rather than solely prescriptive functions.